2019
DOI: 10.1039/c8cy02430h
|View full text |Cite
|
Sign up to set email alerts
|

In situ XAS study of the local structure and oxidation state evolution of palladium in a reduced graphene oxide supported Pd(ii) carbene complex during an undirected C–H acetoxylation reaction

Abstract: In situ XAS is used to reveal the evolution of palladium species during an undirected C–H acetoxylation reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The scope of this reaction is broad and leads to a variety of monofunctionalized heterocycles in good to excellent yields. Several related systems for C­(sp 2 )–H acetoxylation have been developed. …”
Section: Palladium–nhc Complexesmentioning
confidence: 99%
“…The scope of this reaction is broad and leads to a variety of monofunctionalized heterocycles in good to excellent yields. Several related systems for C­(sp 2 )–H acetoxylation have been developed. …”
Section: Palladium–nhc Complexesmentioning
confidence: 99%
“…For comparison, the spectra of Ni(OAc) 2 ⋅ 4H 2 O (Ni 2+ ) was also acquired. The white line intensity of complex 1 is lower than Ni(OAc) 2 ⋅ 4H 2 O, which indicates that the oxidation state of the Ni ion of complex 1 is lower than that of Ni 2+ , Figure 4 [20–21] …”
Section: Resultsmentioning
confidence: 98%
“…Many gas–solid heterogeneous catalytic systems have been studied by in situ XAS, providing valuable insights into their reaction mechanisms. However, traditionally, it has been difficult to obtain in situ XAS data for catalytic systems in suspension or solution due to the challenges associated with the reactor design and the relatively strong interferences of the reaction mixture on X-rays. Fortunately, thanks to recent progress in the field, several successful studies have been reported where the nature of the catalytic species has been elucidated through in situ XAS. …”
Section: Introductionmentioning
confidence: 99%